Identification of Gas Turbine Ground Vortex Formation Regimes - Barata, Jorge M M (2012)
In the present paper the previous work of Barata et al.11 is extended to include eighteen engines that are being used in the present. The ground vortex flows produced by the different engines are compared and discussed for each operational condition. The results have shown that more than one mode can occur for a particular engine-velocity ratio-clearance distance combination with 1, 2 or 3 vortexes that may merge before entering the inlet engine.